Peningkatan Manajemen Pengelolaan Usaha pada UMKM Desa Jeli Tulungagung - Yeni Roha Mahariani; Nouvil Ismi Zam-zam Halim (Kreativasi : Journal of Community Empowerment, 2022)
Exploration of resources in rural areas, especially in Jeli, Tulungagung is an effort that can increase the economic competitiveness of the Jeli community, through entrepreneur programs in various forms of Small and Medium Enterprises (SMEs). SMEs have a role in contributing to increasing regional income and Indonesian income directly or indirectly. In order to improve and develop the existing business potential, community services activities are carried out in Jeli with the target of SME business. The method of implementing this activity includes 5 steps, including (1) the preparation step for industrial visits, (2) the environmental analysis step, (3) the socialization implementation step, (4) the step of tutorial and (5) discussion. Environmental analysis is carried out with the aim of knowing and finding significant problems in the SME management environment. So, it can be used to find out the initial solution to the conditions that exist in the SME environment. The results and activities after the implementation of the socialization are increased understanding of business management on factors of product marketing and business legality. The follow-up to the results of the activities is expected to be carried out on an ongoing basis to improve and develop the potential of SMEs in Jeli.